Development of RCODE Learning Materials to Enhance Students’ Mathematical Creative Thinking Skills Based on Outcome-Based Assessment - Adi Candra Kusuma; Doddy Maulana; Almas Adibah; Muchlis Fajar Hidayat (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
This study aimed to develop RCODE learning materials based on Outcome-Based Assessment (OBA) to improve students’ mathematical creative thinking skills in Fourier series. The study employed a research and development approach based on the Plomp model, comprising the preliminary investigation, design, realization or construction, testing, evaluation, and revision phases. The developed products included a semester learning plan, student assignment plan, teaching module, student worksheets, a mathematical creative thinking skills test, observation sheets, a student response questionnaire, and validation instruments. A limited-scale trial was conducted involving 23 students enrolled in the Applied Bachelor’s Program in Electronics Engineering at the State Polytechnic of Malang. Data were collected through observations, interviews, questionnaires, and tests and were subsequently analyzed in terms of validity, practicality, and effectiveness. The validation results yielded an average score of 3.38 (82.5%), which was categorized as highly valid. The practicality assessment yielded an average score of 3.38 (84.5%), indicating that the learning materials could be implemented effectively and received positive responses from the students. The students’ average score increased from 56.78 on the pretest to 83.58 on the posttest, with an N-Gain score of 0.62, which was classified as moderate. The average achievement score for the indicators of mathematical creative thinking skills was 8.17. Therefore, the OBA-based RCODE learning materials were considered valid, practical, and effective in improving students’ mathematical creative thinking skills